2011
DOI: 10.4061/2011/845170
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Therapies Using Cell Sheet-Based Tissue Engineering for Cardiac Disease

Abstract: At present, cardiac diseases are a major cause of morbidity and mortality in the world. Recently, a cell-based regenerative medicine has appeared as one of the most potential and promising therapies for improving cardiac diseases. As a new generational cell-based regenerative therapy, tissue engineering is focused. Our laboratory has originally developed cell sheet-based scaffold-free tissue engineering. Three-dimensional myocardial tissue fabricated by stacking cardiomyocyte sheets, which are tightly intercon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…When the temperature is dropped below 32°C, the surface becomes hydrophilic and the grafted polymer rapidly hydrates, making it expand and causing the cells to detach from the surface. When compared with enzymatic digestion of a scaffold, which often disrupts the cell-cell contacts, this innovative technology enables a cell sheet to be generated just by cooling the dishes to room temperature and using multiple layered cell sheets (20).…”
Section: Cell Sheet Engineeringmentioning
confidence: 99%
“…When the temperature is dropped below 32°C, the surface becomes hydrophilic and the grafted polymer rapidly hydrates, making it expand and causing the cells to detach from the surface. When compared with enzymatic digestion of a scaffold, which often disrupts the cell-cell contacts, this innovative technology enables a cell sheet to be generated just by cooling the dishes to room temperature and using multiple layered cell sheets (20).…”
Section: Cell Sheet Engineeringmentioning
confidence: 99%
“…In an aqueous environment thermoresponsive surfaces exhibit reversible hydrophobic and hydrophilic properties above and below the lower critical solution temperature (LCST) facilitating the detachment of an intact cell sheet without the use of enzymatic treatments. The efficacy of pNIPAAm for generation of intact cell sheets for skin, cardiac, and periodontal reconstruction have been reported earlier [7, 8]. Copolymerization of pNIPAAm with glycidyl methacrylate allows modulation of LCST and also gives prospects of further modification by incorporation of biomolecules through the epoxy groups of the later [9].…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, such single-cell sheets can be stacked together up to 3 layers (;80 mm) to create a 3D cardiac construct without compromising the viability of the cardiomyocytes. [49][50][51] In vivo studies have demonstrated some functional integration of such cardiac cell sheets with the host myocardium. 52 The source of cardiomyocytes for cardiac cell sheet generation has since been expanded from neonatal rat cardiomyocytes to human cardiac-resident stem cells 53 and cardiomyocytes derived from mouse and human pluripotent stem cells.…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 98%